Prospective for the integration of Blockchain and the IoT for Cluster implementation - Rodríguez Molano, José Ignacio; Martínez Baracaldo, Jhonnatan Nicolás; Triana Casallas, Jenny Alexandra (Ingeniería Solidaria, 2020)
Introduction: The present article is the result of the investigation and approach to the applications and developments of blockchain and Internet of Things (IoT), developed during the second semester of the year 2019 and first of 2020. Problem: Construction of environments and mediums in a cluster structure that allow companies and institutions to cooperate and compete to achieve efficiency and strengthen grouping. Objective: Integrate blockchain and IoT to develop and present a two-level architecture, from which a support environment is established and a series of functionalities are offered for a cluster implementation. Methodology: Review articles to achieve an approach to blockchain and IoT architecture, configuration and description of structural and functional levels. Results: An architecture with a structural level constituted by a decentralized computer application based on blockchains, a sensory and response network that incorporates IoT technologies and an intermediate component of cloud computing; this, at a functional level that manages to offer users support and help in their activities from modules created with a particular specialty. Conclusion: The structural level furthered the integration of base technologies, blockchain and IoT; on the other hand, the second level of architecture reveals the potential and versatility of these technologies. Originality: Proposal for the implementation of blockchain, IoT and cloud computing in a cluster structure. Limitations: The difficulty of accessing a cluster to perform a test of the architecture in a real environment.